Facile and Straightforward Synthesis of Racemic Version of Substituted 3-[3-(2-Hydroxyphenyl)-3-oxo-1-arylpropyl]-4-hydroxycoumarins: Easy Access to a Series of Biorelevant Warfarin Analogues - Brahmachari, Goutam; Mandal, Mullicka; Karmakar, Indrajit (Synthesis, 2021)
The present communication deals with a straightforward, efficient, and green synthesis of a series of racemic version of 3-[3-(2-hydroxyphenyl)-3-oxo-1-arylpropyl]-4-hydroxycoumarins as biologically interesting warfarin analogues upon decarboxylative hydrolysis of bis-coumarin derivatives in aqueous potassium hydroxide solution. The salient features of this practical method are operational simplicity, avoidance of any organic solvents and tedious column chromatographic purification, clean reaction profiles, excellent yields, and gram-scale synthetic applicability.
Keywords: 3-[3-(2-hydroxyphenyl)-3-oxo-1-arylpropyl]-4-hydroxycoumarins; warfarin analogues; water medium; cost-effective; green synthesis